Cognition and Social Behaviors Related to COVID-19 Among Students in Medical Colleges: A Cross-Sectional Study in Guangdong Province of China - Zhang, Qiu; Lu, Xiaoya; Liao, Mengxin; Zhang, Xinyue; Yao, Liqing (Frontiers in Public Health, 2022)
Background The COVID-19 pandemic is a public health emergency of international concern. This study aimed to describe the cognition and social behaviors related to COVID-19 among medical college students in China and to explore the relevant factors that have affected individual social behaviors. The study could enrich practical research on the social behaviors of college students during the COVID-19 pandemic. Methods From February to April 2020, online questionnaire survey was conducted meticulously. Based on their majors, the students were divided into a medical student group (249 cases) and a near-peer medical student group (397 cases). Descriptive statistics was used to elaborate the cognition related to the pandemic and the status quo of social behaviors among these students. A multiple linear regression model was established to analyze the relevant factors affecting individual social behaviors from various perspectives during the pandemic. Results Regarding the cognition situation: 76.32% of those surveyed had good pandemic awareness, and the average general cognition score was 30.55 ± 3.17 points. In terms of social behaviors, the average scores for purposive rational actions and affective actions during the outbreak were relatively high, scoring 8.85 ± 1.72 points (>10 points) and 4.32 ± 1.41 points (>6 points), respectively, while the average value rational actions score was relatively low at 5.95 ± 1.90 points (>10 points). The results of the multiple linear regression model showed that urban college students had higher scores for purposive rational actions; college students with the CCP membership had higher value rational actions scores; school and major were also significant factors affecting affective actions scoring. The COVID-19 cognition score had a significant effect on the social behavior score in all dimensions (P < 0.001). Conclusions The cognition of COVID-19 among students in Chinese medical colleges was good, and pandemic cognition was an important factor that affected individual social behaviors. Universities and colleges should strengthen the publicity and education of knowledge related to COVID-19, guide students to internalize their knowledge of the pandemic into positive behaviors, and help to win the battle of pandemic prevention and control.